A Case of Fragmented High School Earth and Space Science Education in the Great Plains: Tracing Teacher Certification Policy to Students' Access. Issue 3 (7th August 2017) - Lewis, Elizabeth; Lu, Jia
ABSTRACT: Although U.S. high school students' access to Earth and space science (ESS) varies widely from state to state, nationally, ESS content is the most neglected area of science education and scientific literacy. States have been considering whether they will formally adopt, or less formally adapt, the new national science education standards, the Next Generation Science Standards (NGSS), which have been carefully developed and articulated in conjunction with state education leaders. However, there are many challenges with which states, school districts, and teachers must grapple to enact standards-aligned ESS science lessons. This study of one Great Plains state investigated how school districts provide ESS education at the high school level and to what degree is ESS being taught by qualified teachers. We found that 76% of districts added ESS topics to existing physical science and/or biology courses rather than offer a stand-alone ESS course. During the eight-year period investigated, the state awarded 901 science teaching endorsements to either new secondary teachers of which only 3.3% were single-subject ESS endorsements. In Phase I and II of our study we found that only 7% of science teachers teach ESS with an ESS endorsement versus a general science or other science subject area endorsement. When teachers teach ESS out-of-field they lack the confidence and subject matter knowledge to teach effectively using inquiry-based approaches and are less likely to recognize misconceptions and oversimplification of ESS content.